2019
DOI: 10.1016/j.stemcr.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC-Derived Retinas Recapitulate the Fetal CRB1 CRB2 Complex Formation and Demonstrate that Photoreceptors and Müller Glia Are Targets of AAV5

Abstract: Human retinal organoids from induced pluripotent stem cells (hiPSCs) can be used to confirm the localization of proteins in retinal cell types and to test transduction and expression patterns of gene therapy vectors. Here, we compared the onset of CRB protein expression in human fetal retina with human iPSC-derived retinal organoids. We show that CRB2 protein precedes the expression of CRB1 in the developing human retina. Our data suggest the presence of CRB1 and CRB2 in human photoreceptors and Müller glial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
126
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(136 citation statements)
references
References 50 publications
8
126
2
Order By: Relevance
“…AAV is a highly efficient method of delivering therapeutic genes to photoreceptor cells and several AAV based gene therapy trials for monogenic inherited retinal dystrophies are ongoing (for review see ). AAV2/5 has been shown to effectively transduce photoreceptors in a variety of species inter alia mice (Palfi et al, 2012), non-human primates (Boye et al, 2012) and human retinal explants (Wiley et al, 2018, Quinn et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAV is a highly efficient method of delivering therapeutic genes to photoreceptor cells and several AAV based gene therapy trials for monogenic inherited retinal dystrophies are ongoing (for review see ). AAV2/5 has been shown to effectively transduce photoreceptors in a variety of species inter alia mice (Palfi et al, 2012), non-human primates (Boye et al, 2012) and human retinal explants (Wiley et al, 2018, Quinn et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous models in 2D, these 3D structures contain photoreceptors with morphologically identifiable features; including, inner segments rich in mitochondria, rudimentary outer segments with connecting cilia, and synaptic pedicles in addition to bipolar, Müller glia, ganglion and amacrine cells, synaptic layers and an outer limiting membrane, arranged in retinal layers (reviewed in (Castro et al, 2019, Capowski et al, 2019. These advanced models have proven to have many translational research applications, including transplantation studies (Pearson et al, 2016, Gonzalez-Cordero et al, 2017, probing mechanisms of retinal development (Phillips et al, 2014), and specific retinal disease modelling and testing efficacy of potential therapies in human photoreceptor cells (Parfitt et al, 2016, Deng et al, 2018, Schwarz et al, 2017, Sharma et al, 2017, Quinn et al, 2019. To date, however, they have not been used to model and rescue photoreceptor cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside studies demonstrating that different eye cup‐like structures including 3D retinal organoids may provide essential and fundamental insight into developmental and regenerative processes , reports of the utility of these human tissues in eye disease modeling are now emerging (Table ). Most eye diseases involve the dysfunction and degeneration of the retina with blindness as the final outcome, as effective treatments do not currently exist.…”
Section: Retinal Tissue As Disease Modelmentioning
confidence: 99%
“…The works of Phillips et al and Quinn et al demonstrated how hiPSCs‐derived retinal tissue derived from patients could be applied to study genes involved in retinogenesis. In the first study, the authors modeled microphthalmia caused by mutations in the Visual System Homeobox 2 ( VXS2 ) gene by comparing optic vesicles generated from microphthalmia hiPSCs and healthy donor hiPSCs, thereby providing a paradigm for elucidating transcription factors and signaling pathways triggered by this early development associated gene.…”
Section: Retinal Tissue As Disease Modelmentioning
confidence: 99%
See 1 more Smart Citation